Where are we from and where are we? The academic education of Occupational Therapy professors that are working at public Universities in Northeast Brazil. - Chaves Azevedo de Souza, Marina Batista; Marques Duque, Andrezza (Brazilian Journal of Occupational Therapy / Cadernos Brasileiros de Terapia Ocupacional, 2024)
Introduction: The historical process of Occupational Therapy courses in Brazil and the academic profile of their teachers are factors that influence the training of professionals and the scientific development of the profession. Objective: To characterize the academic titles of professors who work in Occupational Therapy courses at public Universities in the Northeast region of Brazil and reflect about institutional and professional trajectories. Method: Descriptive, quantitative study, using public data from the Lattes Platform and official Universities websites. Descriptive statistics and spatial analysis were used to analyze the data using graphic resource and image production software, such as Excel®, PowerPoint® and QGIS2.18.3®. Results: 86 resumes of professors of Occupational Therapy courses at public institutions in the Northeast were analyzed. Only 20% entered with a doctorate or concluded it in the year of admission. The courses in Paraiba and Sergipe received the largest number of professors from other states, especially from the Southeast of the country. There was a greater number of professors who obtained a master's degree in Alagoas, Pernambuco, and São Paulo. Most doctoral degrees took place in Pernambuco and São Paulo. More than 90% of the professors held postgraduate courses in Health Sciences (68%) and Humanities (25%), in Public Health, Education and Health Sciences programs. Conclusion: The institutions have a diverse team of teachers. The academic education was related to physical dislocation in the country. We pointed to the importance of the policies that encourage science in the Northeast because it can strengthen the profession and alleviate regional inequalities.